PENGGUNAAN PENDEKATAN KONTEKSTUAL MODEL KOOPERATIF DALAM PEMBELAJARAN PKn GUNA MENINGKATKAN PRESTASI BELAJAR SISWA - Ngudiono Ngudiono (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2023)
The purpose of research to improve activity learning and achievement learning students in PKn learning through contextual approach by cooperative medel. The metode of research using qualitative approach. Designes of cycle opproach are plan, implementation, observation, and reflection. The subject of research at X grade Multimedia is 44 students. The data collected using abservation, check list and documentation. Analyzing the data linier technique ( stream). The complete resulth research in one cycle from 21 students (47,73%) with average 67,57 and second cycle from 35 students (79,55%) with average 73,52. The conclution of research is activity learning through contextual approach by cooperative model in PKn learning at X grade in one semester of SMK Islam Tikung Lamongan in the academic year 2011/2012 can improve achievement learn student.